1978
DOI: 10.1111/j.1432-1033.1978.tb12584.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Adenylate Cyclase/Cyclic AMP Response by Thyrotropin and Prostaglandin E2 in Cultured Thyroid Cells. 2. Positive Regulation

Abstract: Two different independent processes are operating in cultured thyroid cells to regulate adenylate cyclase/cyclic AMP responsiveness to thyroid stimulators (thyrotropin and prostaglandin Ez) :firstly, refractoriness or negative regulation [preceding paper], which is specific for each thyroid stimulator, is not mediated by cyclic AMP and is not accompanied by alteration of adenylate cyclase activity; secondly, positive regulation which is characterized by an augmentation of the cyclic AMP response stimulated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…4) containing NaCl instead of sucrose, the number of TSH binding sites was reduced by approximately 10-fold, without any alteration in the affinity of TSH binding (data not shown). Previous studies with FRTL5 rat (14) and pig (18) thyroid cells indicate that prolonged (16-24 h) exposure of these cells to TSH reduces the number of TSH receptors available for TSH binding. This TSH receptor down-regulation cannot be the basis for TSH desensitization in FRTL5 thyroid cells because the latter is evident much earlier, within 2 h of TSH stimulation (12).…”
Section: Resultsmentioning
confidence: 98%
“…4) containing NaCl instead of sucrose, the number of TSH binding sites was reduced by approximately 10-fold, without any alteration in the affinity of TSH binding (data not shown). Previous studies with FRTL5 rat (14) and pig (18) thyroid cells indicate that prolonged (16-24 h) exposure of these cells to TSH reduces the number of TSH receptors available for TSH binding. This TSH receptor down-regulation cannot be the basis for TSH desensitization in FRTL5 thyroid cells because the latter is evident much earlier, within 2 h of TSH stimulation (12).…”
Section: Resultsmentioning
confidence: 98%
“…In the thyroid, the expression of NIS is principally regulated by the thyroid-stimulating hormone (TSH) (Kogai et al 1997). When TSH binds to the TSH receptor (TSHR), adenylate cyclase is activated, leading to increased intracellular cAMP levels (Takasu et al 1978), which further activates the transcription factors, cAMP response element-binding protein (CREB) and Pax8 (Poleev et al 1997). The NIS upstream enhancer (NUE), which is fundamental in the initiation of NIS transcription, contains binding sites for both Pax8 and CREB, which stimulate NIS transcription upon transcription factor binding (Ohno et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The fourth possibility seems also to be unlikely, since phos¬ phodiesterase activity has been reported to increase by chronic stimulation with endogenous TSH (Bastomsky et al 1971). On the other hand, Takasu et al (1978) reported that adenylate cyclase activity in cultured porcine thyroid cells was decreased when cultured without TSH as compared to when cultured in 5-50 µ /ml of TSH.…”
Section: Discussionmentioning
confidence: 94%